Respectability on trial: sex crimes in New York City, 1900-1918 - Donovan, Brian (SUNY Press, 2016)
Acknowledgments -- Introduction -- Trials of the first sexual revolution -- Date rape and the crime of seduction -- Rape and the double bind of progressive-era femininity -- White slaves and ordinary prostitutes -- Sodomy, manhood, and consent -- Conclusion: rethinking sexual revolution -- Notes -- Bibliography -- Index